2012
DOI: 10.3390/s121217588
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Monitoring of Soil Water Content and Salinity with a Low-Cost Capacitance-Resistance Probe

Abstract: Capacitance and resistivity sensors can be used to continuously monitor soil volumetric water content (θ) and pore-water electrical conductivity (ECp) with non-destructive methods. However, dielectric readings of capacitance sensors operating at low frequencies are normally biased by high soil electrical conductivity. A procedure to calibrate capacitance-resistance probes in saline conditions was implemented in contrasting soils. A low-cost capacitance-resistance probe (ECH2O-5TE, 70 MHz, Decagon Devices, Pull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 42 publications
2
57
0
1
Order By: Relevance
“…They also stated that the older type ECH 2 O EC-20 was more sensitive to bulk electrical conductivity than ECH 2 O EC-5. Scudiero et al [53] suggested using a newer version of ECH 2 O TE, ECH 2 O 5TE, which works at a frequency of 70 MHz for continuous monitoring of soil moisture content and solute dynamics in saline soils. …”
Section: Discussionmentioning
confidence: 99%
“…They also stated that the older type ECH 2 O EC-20 was more sensitive to bulk electrical conductivity than ECH 2 O EC-5. Scudiero et al [53] suggested using a newer version of ECH 2 O TE, ECH 2 O 5TE, which works at a frequency of 70 MHz for continuous monitoring of soil moisture content and solute dynamics in saline soils. …”
Section: Discussionmentioning
confidence: 99%
“…The coaxial terminal open circuit reflection method was used to determine the complex dielectric constant within a frequency range of 10 MHz to 1 GHz (Sakellis et al, 2014;Scudiero et al, 2012). Fig.…”
Section: Complex Dielectric Constantmentioning
confidence: 99%
“…According to organic principles, monitoring of the pesticide content and the impact of food processing on the food quality seems of high relevance . The uses of nanoparticles in sensors and software are being designed to determine salinity and water requirements in the field while increasing the yield and saving water . Although nanosensors can assist farmers in maintaining precise control of their crops, research efforts to develop the nanosensors will be vital to aid decision‐making in crop protection, monitor nutrient profiles, recommend pesticide dose, and enable real‐time monitoring of soil parameters (residual pesticides, nutrients, pH and soil humidity) .…”
Section: Nanotechnology‐based Sensing Opportunities In Agriculturementioning
confidence: 99%